Methadone-maintained patients in primary care have higher rates of chronic disease and multimorbidity, and use health services more intensively than matched controls. (December 2014) - O'Toole, John; Hambly, Róisín; Cox, Anne-Marie; O'Shea, Brendan; Darker, Catherine
Abstract Background: Methadone maintenance treatment in primary care is cost-effective and improves outcomes for opiate-dependent patients. A more developed understanding of the evolving needs of this important cohort will facilitate further improvements in their integrated care within the community. Objectives: The aim of this study was to compare the burden of chronic disease, multi-morbidity and intensity of health-service use between methadone-maintained patients (MMPs) and matched controls in primary care. Methods: This is a retrospective matched case-control design. Data on chronic disease and health service use was collected in 13 computerized GP surgeries on 414 patients (207 MMPs and 207 controls). Twelve months of records were examined. MMPs were compared with controls matched by gender, age, socio-economic status (SES) and GP surgery. Results: MMPs suffered more chronic disease (OR = 9.1, 95% CI: 5.4–15.1, P < 0.001) and multi-morbidity (OR = 6.6, 95% CI: 4.3–10.2, P < 0.001). They had higher rates of respiratory, psychiatric and infectious disease. MMPs of lower SES had more chronic disease than their peers (OR = 7.2, 95% CI: 2.4–22.0, P < 0.001). MMPs attended the doctor more often with medical problems (OR = 15.4, 95% CI: 8.2–28.7, P < 0.001), with a frequent requirement to have medical issues addressed during methadone-management visits. Their care generated more telephone calls (OR = 4.4, 95% CI: 2.8–6.8, P < 0.001), investigations (OR = 1.8, 95% CI: 1.2–2.7, P = 0.003), referrals (2.6, 95% CI: 1.7–4.0, P < 0.001), emergency department visits (2.1, 95% CI: 1.3–3.6, P = 0.004), outpatient attendances (2.3, 95% CI: 1.51–1.43, P < 0.001) and hospital admissions (3.6, 95% CI: 1.6–8.1, P = 0.001). Conclusion: Correcting for routine methadone care and drug-related illnesses, MMPs had a higher burden of chronic disease and used both primary and secondary health services more intensively than matched controls.